Optical microscopy of fiber reinforced composites - Hayes, Brian S.; Gammon, Luther M. (Materials Park, Ohio : ASM International, 2010)
Optical microscopy is one of the most valuable--but under utilized--tools for analyzing fiber reinforced polymer matrix composites. This hands-on instructional book covers everything: sample preparation, microscopic techniques, and applications. The power of optical microscopy to study the microstructure of these heterogeneous, anisotropic materials is illustrated with over 180 full color images.
Preface -- Acknowledgments -- Introduction : composite materials and optical microscopy -- Sample preparation and mounting -- Rough grinding and polishing -- Special sample preparation and polishing -- Viewing the specimen using reflected-light microscopy -- Thin-section preparation and transmitted-light microscopy -- Composite structure analysis -- Void analysis of composite materials -- Microcrack analysis of composite materials -- Toughening methods for thermoset-matrix composites -- Impact response of composites -- Matrix microstructural analysis -- Honeycomb-cored sandwich structure composites -- Surface degradation of composites -- The effects of lightning strikes on polymeric composites.
Includes bibliographical references and index.
Print version record.
English.
Added to collection customer.56279.3
Keywords: Fibrous composites; Microscopy; Composite materials; Composites à fibres; Microscopie; Composites; fibrous composite; microscopy; composite material; TECHNOLOGY & ENGINEERING -- Material Science; Composite materials; Fibrous composites; Microscopy